2018
DOI: 10.1128/mbio.00420-18
|View full text |Cite
|
Sign up to set email alerts
|

The Origin, Dynamic Morphology, and PI4P-Independent Formation of Encephalomyocarditis Virus Replication Organelles

Abstract: Picornaviruses induce dramatic rearrangements of endomembranes in the cells that they infect to produce dedicated platforms for viral replication. These structures, termed replication organelles (ROs), have been well characterized for the Enterovirus genus of the Picornaviridae. However, it is unknown whether the diverse RO morphologies associated with enterovirus infection are conserved among other picornaviruses. Here, we use serial electron tomography at different stages of infection to assess the three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 52 publications
6
56
0
Order By: Relevance
“…Our results add to studies that, in the last years and after much speculation, have started to provide experimental evidence that the DMVs induced by +RNA viruses are active sites of vRNA synthesis [11, 5860]. However, it is not clear that DMVs always play the primary role in virus replication that we demonstrate here for CoV.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Our results add to studies that, in the last years and after much speculation, have started to provide experimental evidence that the DMVs induced by +RNA viruses are active sites of vRNA synthesis [11, 5860]. However, it is not clear that DMVs always play the primary role in virus replication that we demonstrate here for CoV.…”
Section: Discussionsupporting
confidence: 68%
“…However, it is not clear that DMVs always play the primary role in virus replication that we demonstrate here for CoV. For picornaviruses, for example, virus-induced single membrane structures, which are DMV precursors and also active sites of vRNA synthesis, could well be more relevant as they predominate at the peak of vRNA replication [10, 11, 60]. By clearly pointing to DMVs as the key sites for CoV replication, our results also bring back to centre stage some of the challenges that CoV-induced DMVs pose, which extend to the distantly-related arterivirus family, and probably also to other members of the order Nidovirales .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, many studies have demonstrated the power of these methods. Structures harboring the VRCs such as single-membrane spherules and double membrane vesicles have been studied in detail within the replication organelles of West Nile Virus (Gillespie et al, 2010), HCV (Romero-Brey et al, 2012), coxsackievirus B3 (Limpens et al, 2011), Bunyamwera virus (Fontana et al, 2008), Rubella virus (Fontana et al, 2010), Tombusvirus (Fernández de Castro et al, 2017a), a cardiovirus (Melia et al, 2018) and the human reovirus (Fernández de Castro et al, 2014a;Tenorio et al, 2018). The reovirus replication neoorganelle visualized in 3D with two different methods is shown in Fig.…”
Section: D Imaging/tomographymentioning
confidence: 99%
“…Lack of cell membrane visibility was proclaimed either due to extraction of lipids or to the failure of the bilayer membrane to bind electron-dense fixatives or stains. Addition of water to the substitution medium was shown to considerably improve membrane visibility (Limpens et al, 2011;Melia et al, 2018). The FS media used in this study contained more water and although was shown to clearly preserve the Golgi bodies, it is not clear why the cell membrane complexes are not visible in the follicles.…”
Section: Preservation Of Key Aspects Of Follicle Biologymentioning
confidence: 82%